Organic waste - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Organic waste: options for small-scale resource recovery edited by Inge Lardinois and Arnold van de Klundert 1993 132pp ISBN 90 70857 332 TOOL, Sarphatistraat 650, 1018 AV, Amsterdam, THE NETHERLANDS